Do workers with self-reported symptoms have an elevated risk of developing upper extremity musculoskeletal disorders three years later? - Descatha, Alexis (BMJ Group, 2008)
OBJECTIVES: Few prospective studies have evaluated outcomes of workers with self-reported symptoms of upper extremity musculoskeletal disorders (UEMSD). Our objective was to study the three-year outcomes of workers with self-reported symptoms, with or without a positive physical examination. METHODS: In 1993–1994, 598 subjects highly exposed to repetitive work filled out a Nordic-style questionnaire. They underwent a standardised physical examination at that time and again in 1996–1997 by the same occupational physician. The three-year outcomes (based on physical examination) of workers with a self-administered questionnaire positive at baseline for UEMSD, with or without a positive physical examination, were studied. RESULTS: The three-year incidence rate was 44.1%, with one third of these incident cases who had self-reported symptoms in 1993–1994. Workers with a positive questionnaire had a significantly higher risk of UEMSD at physical examination three year later (80.1% UEMSD cases with positive questionnaires n=354, versus 44.2% cases without positive questionnaires n=69, p<0.0001). Moreover, workers with positive questionnaires but without UEMSD diagnosed in 1993–1994 (n=177) had also a significantly higher risk of UEMSD at physical examination three years later (60.5% cases with positive questionnaires n=26, versus 38.8% cases without positive questionnaires n=52, p=0.01). Results were similar when gender and age were taken into account. CONCLUSION: Workers highly exposed to repetitive movements had a high risk of developing UEMSD and should be followed closely in surveillance programmes. Workers with self-reported symptoms without UEMSD diagnosed in physical examination represented only one third of new cases three years later. However, their risk to develop UEMSD was significantly increased, compared with those without symptoms.